Study of Collision and Radiative Stopping Power of Electron for Blood, Bone, and Adipose Tissue - O. Kadhim, Rashid; S. Ali, Niran (International Journal of Psychosocial Rehabilitation, 2020)
The mass collision stopping power ((dE/ρdx)col), the mass radiative stopping power ((dE/ρdx)rad), and the total mass stopping power of electrons in the energy range of 0.01–1000 MeV have been calculated for blood, bone, and adipose tissue. The results of the present work for the collision stopping power of electrons in blood, bone, and adipose tissue are in good agreement with the standard results given by the ESTAR program. The radiative stopping power of electrons in the same energy range is also calculated using a modified equation, and the results are found to be in agreement with the standard published values. The employed modified equation used to calculate the radiative energy loss of electrons is valid in the energy range of electrons from 0.01 to 1000 MeV and gives accurate results. As far as the results of the total stopping power calculation are concerned, they are found in good agreement with the published results, where the error is less.